The Application of Chemical Castration Punishment to Child Sexual Violence Perpetrators from the Perspective of Indonesian Criminal Law - ISDITTA CHAULA LIANI; RASDI, S. Pd., M.H. (Law Research Review Quarterly, 2026)
The phenomenon of sexual violence against children in Indonesia has reached a state of emergency, prompting the government to establish chemical castration sanctions through Law No. 17 of 2016 and Government Regulation No. 70 of 2020. However, this policy has sparked debate regarding the disharmony of norms with the sentencing system in the Criminal Code (KUHP) and ethical obstacles within the medical profession regarding its implementation. This study aims to analyze the legal standing of chemical castration from the perspective of Indonesian criminal law and identify the juridical obstacles hindering its effective implementation. The research method employed is normative juridical with a statutory approach (statute approach). Data were collected through literature studies of primary and secondary legal materials and subsequently analyzed qualitatively. The results indicate a legal ambiguity regarding the status of chemical castration, oscillating between a criminal penalty (straf) and a treatment measure (maatregel). Although Law No. 1 of 2023 (the New Criminal Code) adopts a corrective justice paradigm, synchronization of norms remains necessary to ensure the policy has a solid legal foundation. Primary implementation obstacles include the refusal of medical personnel based on professional ethics, limited facilities, and a lack of clarity in execution mechanisms. This study recommends an evaluation of technical regulations to guarantee legal certainty and maximum protection for children without disregarding human rights principles.